Konseling Islam melalui Teknik Ta’limah dan Muhasabah dalam Mengubah Perilaku PSK di Situbondo - Moh. Fadlur Rahman; Abd. Mughni; Akhmad Zaini (Fakultas Dakwah Universitas Ibrahimy, 2021)
Islamic counseling is the provision of assistance by an expert called a counselor to individuals who have problems using the concept of Islamic teachings, namely the Qur'an and al-Hadith whose problems are resolved leading to the counselee, so that they can obtain happiness in the world and the hereafter. This study aims to describe the Islamic counseling process through ta'limah and muhasabah techniques in changing the behavior of PSK The conclusion of this research is Islamic counseling through ta'limah and muhasabah techniques in changing the behavior of sex workers in Situbondo in the success of their guidance, mentors not only teach Islamic religious teachings (ta'limah), but they are also taught to become individuals who can be aware, know their true identity. themselves by doing muhasabah or self-introspection which is preceded by a good and correct understanding of the religion of Islam, so that they are always enthusiastic about the teachings and guidance given and then can make them continue to worship, dhikr and recite the Koran togethe